Improving sales and marketing collaboration : a step-by-step guide - Malshe, Avinash; Biemans, Wim G., 1960- (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
In any company, sales and marketing are the two primary business functions that are focused on creating satisfied customers. Because of their complementary orientations and objectives, these two functions are ideally positioned for a fruitful, synergetic collaboration. Unfortunately, the practical reality in many companies is far removed from this utopia. Sales and marketing personnel fail to communicate effectively, resulting in misunderstandings, lack of communication, frustration, and sometimes even downright anger and sabotage. Instead of supporting each other in creating superior value for customers, sales and marketing fight tiresome internal battles that are a drain on profits, efficiency and customer satisfaction.
Preface -- Introduction -- Working together to create value for customers -- Sales and marketing don't always get along -- Taking a look under the hood of the interface -- Mending the rift between sales and marketing -- Assessing your sales-marketing interface -- Challenges to your sales-marketing interface -- Appendix. The sales-marketing huddle: workshop template -- About the authors -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 179-183) and index.
Title from PDF title page (viewed on December 21, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Sales management; Marketing -- Management; sales-marketing relationship; sales-marketing alignment; managing sales-marketing interface; Electronic books